Improving schools through action research : - Hendricks, Cher (Allyn & Bacon, 2009)
This text emphasizes the reflective processes used in planning and conducting action research studies, data analysis techniques (quantitative and qualitative), and displaying and explaining results. It provides specific information needed to complete each step of the action research cycle with chapter activities that help the student/reader conduct projects focused on school improvement. Each activity includes a research paper component that helps students create a research paper as they complete the activities.